Catalytic biomass gasification in decoupled dual loop gasification system over alkali-feldspar for hydrogen rich-gas production. (June 2022) - Khan, Muhammad Mahmood; Xu, Shaoping; Wang, Chao
Abstract: Gasification of biomass with steam and oxygen was carried over alkali-feldspar in a decoupled dual loop gasification (DDLG) system. This system has a moving bed reformer (MBR), a fluidized bed gasifier (FBG), a riser combustor (RC) and a particle grading cyclone (PGC). Through the PGC, two loops, i.e. a gasification loop of FBG-RC-PGC utlizing quartz sand as circulating bed material and a reforming loop of MBR-RC-PGC utilizing alkali-feldspar as circulating bed material, are formed. The effects of process variables such as reformer temperature, steam to biomass ratio (S/B) and air equivalence ratio (ER) on product gas composition, heating value, tar content, yield of product gas, carbon conversion, water conversion and cold gas efficiency were investigated. The maximum water conversion 35.2% and cold gas efficiency 82.3% were observed at reformer temperature 850 °C. The increase of S/B promoted the H2 -rich gas production and the maximum concentration of 42.1 vol % was achieved at the S/B of 1.0. In addition, the use of steam and oxygen together as gasification agent enhanced the tar removal and carbon conversion. The lowest tar content 1.1 g/Nm 3 and high carbon conversion 97.2% were obtained at S/B of 0.6 and ER of 0.35. Graphical abstract: Image 1 Highlights: Alkali-feldspar utilized as an in-situ catalyst in the decoupled dual loop gasifier. Tar content significantly reduced at high ER and with alkali-feldspar catalyst. Gasifier and reformer reactions decoupling enhanced product gas quality and tar removal.